Repression via DNA looping by the Gram-positive global transcriptional regulator ScoC from Geobacillus - Smadar Shulami; Noam Hadad; Mnar Ghrayeb; Sergei Pomyalov; Yael Pazy; Liraz Chai; Yuval Shoham; Gil Shoham (Communications Biology)
Abstract ScoC of the MarR family is a global regulator of transition phase pathways in Gram-positive bacteria, and in Bacillus subtilis it is estimated to regulate more than 500 genes. ScoC mediated activity is governed by its regulated expression, and by the interplay with other global transcriptional factors allowing for the finetuning of gene expression. Here we show, by transcriptional lacZ-fusions analysis, that ScoC from Geobacillus binds to two operator sites in the promoter region of the oligopeptide permease oppA, and that both binding sites are necessary for repression. Gel retardation assays, atomic force microscopy and fluorescence resonance energy transfer analyses demonstrate that ScoC can induce DNA looping. The crystal structures of ScoC and ScoC complexed with a 23-bp symmetric palindromic DNA from Geobacillus were determined at 3.15 Å and 3.50 Å resolution, respectively. The structures revealed a tetrameric X-shaped assembly composed of two dimers in which each dimeric unit comprises a winged helix-turn-helix DNA-binding motif. Our results expand the architecture of the MarR family regulators and suggest a mechanism by which ScoC interacts with other regulatory factors to modulate gene expression in the transition phase.